JURIDICAL ANALYSIS OF INTERNATIONAL PERMANENT COURT OF ARBITRATION AWARD OF 12 JULY 2016 REGARDING SOUTH CHINA SEA DISPUTE AND ITS IMPACT FOR INDONESIA - Lilis Rahmawati; Nellyana Roesa (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2021)
Abstrak – The provisions regarding International Maritime boundaries have been regulated significantly under UNCLOS 1982, one of the maritime boundaries set in UNCLOS is related to Exclusive Economic Zones boundaries, which regulated in Article 55 of UNCLOS 1982. According to “historic rights”, China has breached these provisions by established the nine-dash line in the South China Sea and it gives impact to other states including Indonesia’s EEZ in Natuna waters.This study analyses about International Permanent Court of Arbitration award of 12 July 2016 regarding the South China Sea dispute and to find out the impact of the International Permanent Court of Arbitration Award of 12 July 2016 in the South China Sea to Indonesia. The research was used normative legal research and analyze the award by finding out the relevant rules. The outcome of this study indicates that China does not have a legal basis to claim the South China Sea and it was contradicted the provisions in UNCLOS 1982. The Tribunal award could be a basis for Indonesia in maintaining its territory from China’s claim. The recommendation for China is China should respect to the Tribunal award and Indonesia should also take any decisive actions regarding China’s claim in the Natuna waters as Indonesia’s Exclusive Economic Zones. Keyword : Historical claim, Natuna waters, Permanent Court of Arbitration, South China Sea